2016
DOI: 10.1007/s12035-015-9628-x
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Responses in Rat and Mouse Models of Radiation-Induced Brain Injury

Abstract: The brain is the major dose-limiting organ in patients undergoing radiotherapy for assorted conditions. Radiation-induced brain injury is common and mainly occurs in patients receiving radiotherapy for malignant head and neck tumors, arteriovenous malformations, or lung cancer-derived brain metastases. Nevertheless, the underlying mechanisms of radiation-induced brain injury are largely unknown. Although many treatment strategies are employed for affected individuals, the effects remain suboptimal. Accordingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 106 publications
5
86
0
Order By: Relevance
“…Exocytosis and vesicle secretion can further facilitate release of purinergic nucleotides, inflammatory molecules, enzymes, and ROS into the extracellular milieu, which collectively can alter the TME to become pro-tumorigenic (60,68,(80)(81)(82) [ Figure 5B]. The dose and time-dependence of radiation exposure can significantly alter the impact of RT on tumor microenvironment by affecting tumor or stromal cell behavior, migration, and treatment response (26,28,29,(83)(84)(85)(86)(87)(88)(89)(90). High-dose irradiation effects include hemorrhage, cognitive decline, neurodegeneration, and premature senescence, which can progress over time (91,92).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exocytosis and vesicle secretion can further facilitate release of purinergic nucleotides, inflammatory molecules, enzymes, and ROS into the extracellular milieu, which collectively can alter the TME to become pro-tumorigenic (60,68,(80)(81)(82) [ Figure 5B]. The dose and time-dependence of radiation exposure can significantly alter the impact of RT on tumor microenvironment by affecting tumor or stromal cell behavior, migration, and treatment response (26,28,29,(83)(84)(85)(86)(87)(88)(89)(90). High-dose irradiation effects include hemorrhage, cognitive decline, neurodegeneration, and premature senescence, which can progress over time (91,92).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic alterations may be pro-tumorigenic, promoting glioma initiation and progression (21)(22)(23)(24). RT-induced metabolic changes in GBM depend on tumor volume, location, and dose-time regime of RT-administration, all of which can vary treatment response (8,(25)(26)(27)(28)(29). While differential metabolism of glioma tumor cells can be targeted to regress tumor growth, understanding the impact of radiation-induced metabolic alterations in GBM microenvironment can provide new avenues to maximize long term benefits of RT in GBM care.…”
Section: Introductionmentioning
confidence: 99%
“…Rodents, including mice and rats, are the most commonly utilized animal models in medical research given their genetic background, anatomical structure, operability, and relatively low cost of use [11]. Experimental data indicated that rodents showed similar anatomical …”
Section: The Establishment Of Rodent Modelsmentioning
confidence: 99%
“…In addition, mice are too fragile to undergo repeated anesthesia when long-term observation periods are required. Therefore, rats are utilized more frequently than mice in radiation-based studies [11]. Nonetheless, no abundant research has compared the difference of radiation-induced cognitive dysfunction between different species and strains of rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, radiation‐induced brain injury is the most common dose‐limiting complication of patients receiving radiotherapy for malignant brain and neck tumors or lung cancer‐derived brain metastases (Yang et al. ). Radiation‐induced brain injury is a dynamic complex process, which includes acute, early delayed and late delayed damage based on the time course and clinical manifestations (BĂ©hin & Delattre, ).…”
Section: Introductionmentioning
confidence: 99%